A CRIANÇA COM AUTISMO, A AFETIVIDADE E A BRINQUEDOTECA - Monteiro, Emilene Gomes (2020)
This study main goal is the analysis of the affectivity configuration in the relation between children diagnosed with autism and the other children and adults, in a university toy library. As specific objectives the study aimed at: identifying the situati